The Influence Of Halal Awareness, E-Wom, And Trust On Repurchase Intention Of Wardah Consumers In Bojonegoro - Ayu Tri Karfina; Yolanda Soedibyo (International Journal of Economics Accounting and Management, 2025)
Indonesia as a country with a majority Muslim population, has strict regulations regarding halal products. When buyers are satisfied with the products they have purchased, they will make repeat purchases. There are several factors that influence repeat purchases, including halal awareness, high e-WOM intensity, e-WOM opinion valence, and e-WOM credibility. This study aims to determine whether these factors influence repurchase intentions for Wardah products in Bojonegoro with trust as an intervening variable. This study uses a quantitative method based on statistical information with a survey as the main method of data collection. The population of this study was Wardah consumers in Bojonegoro, with a sample size of 150 people determined based on the side probability technique. The data analysis method uses SPSS ver. 25 using a regression equation. The results of the study indicate that Halal Awareness has a significant effect on Trust, High Intensity e-WOM on Trust, Valance of Opinion e-WOM has a significant effect on Trust, Credibility e-WOM has a significant effect on Trust, Trust has a significant effect on Repurchase Intention